Making states for the single market: European integration and the reshaping of economic states in the Southern and Eastern peripheries of Europe. Issue 4 (4th July 2017) - Bruszt, Laszlo; Vukov, Visnja
Abstract: European integration has profoundly reshaped states in Europe's peripheries. It has deprived them of the traditional means of autonomously managing development, imposed institutions defending the integrity of the regional market from domestic actors, and provided them, in exchange, with EU-level development policies. However, whereas in the South the EU has relied primarily on incentives for remaking the economic state, in the East it has engaged in direct institution-building. The different EU strategies pushed the evolution of the economic state in the two peripheries in different directions and the two parts of Europe now face different developmental dilemmas. Despite their differences, neither the Eastern nor the Southern states have the capacity to get in synch the triple challenge of integration: playing by the uniform regional rules, improving their positions in the European markets and extending the range of domestic beneficiaries of integration. While the ensuing economic and political tensions might endanger regional integration, EU-level capacities for addressing the developmental problems of the peripheries are in short supply.